Różnorodność jako przejaw innowacyjności / Diversity as a Sign of Innovation - Iwona Koza (Language, Culture, Politics)
Innovation is perceived as a key factor contributing to the competitiveness of organizations and economy, which results in development. One of the internal conditions influencing innovation is diversity. In order to find appropriate, reliable data, it is worth reaching for the indicators that make up the European Innovation Scoreboard 2021, and trace the dynamics of changes in the selected indicators within the last few years. The results obtained in this way give hope for a successful development of economy in the future, and the multiplication of attitudes supporting diversity, supporting innovation and creativity. In the modern world, plagued by numerous crises, these are key issues.